Allhoff on Business Bluffing - Varelius, Jukka (Journal of business ethics, 2006)
The moral status of business bluffing is a controversial issue. On the one hand, bluffing would seem to be relevantly similar to lying and deception. Because of this, business bluffing can be taken to be an activity that is at least prima facie morally condemnable. On the other hand, it has often been claimed that in business bluffing is part of the game and that therefore there is nothing morally questionable in business bluffing. In a recent issue of this journal, Fritz Allhoff puts forward a novel defence of business bluffing. In this article, I will examine Allhoff’s arguments for the moral acceptability of business bluffing and argue that they are implausible.